1995
DOI: 10.1111/j.1365-2672.1995.tb02840.x
|View full text |Cite
|
Sign up to set email alerts
|

Purification and properties of three esterases from Brevibacterium sp. R312

Abstract: C. LAMBRECHTS, J. ESCUDERO AND P. GALZY. 1995. The esterases of Brevibacterium sp. R312 were found to have an intracellular location. Electrophoresis of lysed cell supernatant fluids revealed seven bands of esterase activity in the presence of α‐naphthyl acetate. Eight esterases were separated by anion exchange chromatography. The three main esterases (esterase 4b, 2 and 4a) of Brevibacterium sp. R312 were purified. The molar masses, the pH optima, the temperature optima and heat stabilities were determined. E… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

1997
1997
2010
2010

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 15 publications
0
10
0
Order By: Relevance
“…It was reported that Bacillus licheniformis esterase and Brevibacterium sp. R312 esterase 4a had maximum activity at pH 8.0 with p-nitrophenyl caproate and pNPA, respectively [34,35]. buffers.…”
Section: Determination Of Enzymatic Activitymentioning
confidence: 96%
“…It was reported that Bacillus licheniformis esterase and Brevibacterium sp. R312 esterase 4a had maximum activity at pH 8.0 with p-nitrophenyl caproate and pNPA, respectively [34,35]. buffers.…”
Section: Determination Of Enzymatic Activitymentioning
confidence: 96%
“…Lipolysis occurs to a small degree in most cheese varieties and is only especially marked in mould‐ripened varieties, due mainly to very active extracellular lipases produced by Penicillium roqueforti or P. camemberti , and in hard Italian cheeses manufactured with rennet paste containing pregastric lipase and esterases (Fox & Stepaniak 1993). Lactic acid bacteria are considered to be weakly lipolytic compared with the activities of psychrotrophs, micrococci or brevibacteria (Kalogridou‐Vassiliadou 1984; Bhowmik & Marth 1990; Lambrechts et al . 1995), and little is known about their contribution to cheese lipolysis and flavour development.…”
mentioning
confidence: 99%
“…To determine whether these bands contained catalytic activity of potential relevance to food industry applications and applied enzymology, we subjected them to electrophoretic separation and zymography with alpha-naphthyl acetate, a substrate which has proven useful for the detection of hydrolase activities [15,22,31]. This method was very sensitive, allowing the detection of proteins that were either recalcitrant to silver staining, or present in amounts below the detection limits of silver stain.…”
Section: Discussionmentioning
confidence: 99%
“…The presence of multiple carboxylesterases in a cheese ripening microorganism, Brevibacterium sp. R312 [22], and Aspergillus niger CLP [13] would exert the same effect.…”
Section: Lipase and Ce Activities On Sds-page Gelsmentioning
confidence: 92%
See 1 more Smart Citation